How Canadian Intelligence is Exposed to the Impact of Globalization - Sarah Meyers (The Journal of Intelligence, Conflict and Warfare, 2018)
It could be argued that Canadian intelligence has been negligent toward the impact of globalisation when assessing the security threat of right-wing extremism (RWE), specifically with the advent of the internet and the significant reduction of the influence of state borders on national policy objectives, and therefore has exposed itself to the potential of intelligence failure. This paper is focused on the state of right-wing extremism in Canada through which it addresses the security question: How is Canadian intelligence exposed to the impact of globalisation? The results of this paper are informed by an in-depth analysis of peer-reviewed articles from Canada, the United States (US), and Europe, as well as Canadian government documents, and newspaper articles, as well as the completion of a key assumptions, check to address bias and better evaluate the evidence found. This paper concludes that it appears likely that Canadian intelligence may not be assessing RWE threats through the lens of globalisation. It could be argued that this creates the potential for intelligence failure. However, there remains one significant caveat. It can be interpreted in Public Safety Canada’s latest update that RWE may soon be considered a type of terrorism. If this is the case, the evidence proves that Canadian intelligence may in fact be considering the impact of globalisation in the context of terrorism and therefore would likely implement the same consideration for RWE.